2004
DOI: 10.1183/09031936.04.00133703
|View full text |Cite
|
Sign up to set email alerts
|

Bench testing of auto-adjusting positive airway pressure devices

Abstract: Continuous positive airway pressure devices are routinely used to treat sleep breathing disorders. Automated devices that adjust the therapeutic pressure have recently been proposed. The utility of such devices is still controversial, as rigorous clinical comparisons are difficult to perform as a result of patient and device differences.The current authors studied automated devices in a respiratory model that was able to mimic upper airway mechanics and to interact with pressure adjustment in a closed loop. Fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 38 publications
1
26
0
2
Order By: Relevance
“…Bench studies have indicated that autoCPAP devices variably respond to certain types of simulated hypopnoeas and demonstrate delays when responding to apnoeas [12,13,[17][18][19]. Numerous clinical studies have reported high proportions (17-29%) of under-treated patients on autoCPAP and fixedpressure CPAP therapy [8,9,20,21].…”
Section: Sleep-related Disordersmentioning
confidence: 99%
“…Bench studies have indicated that autoCPAP devices variably respond to certain types of simulated hypopnoeas and demonstrate delays when responding to apnoeas [12,13,[17][18][19]. Numerous clinical studies have reported high proportions (17-29%) of under-treated patients on autoCPAP and fixedpressure CPAP therapy [8,9,20,21].…”
Section: Sleep-related Disordersmentioning
confidence: 99%
“…Bench studies have been proposed to evaluate the responses of APAP devices in different conditions, such as the presence of predefined sleep disordered breathing (SDB) patterns and air leak, [18][19][20][21][22][23][24][25] whereas no such study to date has focused on pressure-relief CPAPs and APAPs. We investigated seven pressure-relief features developed by three CPAP device manufacturers with a previously reported bench model.…”
Section: 17mentioning
confidence: 99%
“…A similar system to that described by Abdenbi et al 9 was set in the bench. In short, a cylindrical transparent chamber (200 mm long, 60 mm external diameter) containing a compliant rubber tube was connected to 2 pumps (KMP830KNDC, KNF Neuberger GmbH, Freiburg, Germany), which supplied continuous positive and negative pressures and controlled the pressure surrounding the tube inside the chamber (P ch ).…”
Section: Starling Resistormentioning
confidence: 99%
“…9 A pneumotachograph (PN279331, Hamilton Medical, Bonaduz, Switzerland) was connected downstream to the mask, and the airflow was measured by a differential pressure transducer (Honeywell DC001NDC4). In addition, another 2 pressure sensors (Honeywell DC030NDC4) were placed in the circuit to record the mask pressure (P m ) and the tracheal pressure (P tr ).…”
Section: Patient Circuitmentioning
confidence: 99%
See 1 more Smart Citation